Loading...

2x^2 - 8x - 48 = 2(x^2 - 4x - 24)

If you mean: x^2+2x-48 then it is (x-6)(x+8) when factored

In order to find the slope, you need to get y by itself.Follow the equation: y = mx + bm = slope-48 = 2x - 8ySubtract 2x from both sides of the equation.-2x - 48 = (2x - 2x) - 8y(I find it easier to have y first in the equation, but either way is fine.)-8y = -2x - 48Divide every number by -8.-8y/-8 = (-2x/-8) + (-48/-8)y = 1/4x + 6y = mx + bm = 1/4

-x2 + 2x + 48 = (x +6)(8 - x)

-x2 + 2x + 48 = (-x - 6)(x - 8)

x2 + 2x - 48 = x2 + 8x - 6x - 48 = x(x + 8) - 6(x + 8) = (x - 6)(x + 8)

-x2 + 2x + 48 = (-x - 6)(x - 8)

Let x = 3 2x + 48 = 2(3) + 48 = 6 + 48 = 54

48

X^2 - 2X - 48 = 0 what two factors of - 48 add up to - 2 ? (X + 6)(X - 8) X = - 6 --------- X = 8 ---------by inspection can solve many quadratics

-x2 + 2x + 48 = (-x - 6)(x - 8) = -(x + 6)(x - 8)

Suppose the first number is 2x (rather than x, so that you force it to be even), where x is an integer. Then the next (consecutive) even number is 2x+2. So the equation is: 2x * (2x+2) = 48

2x - (8 x 6) = 20 2x = 20 + 48 2x = 68 x = 68/2 x = 34

You gave a quadratic expression, not equation. Assuming you mean: 2x - 48 - x^2 = 0 Rearrange into standard form ax^2 + bx + c = 0: -x^2 + 2x - 48 =0 You could directly apply the quadratic formula with a = -1, b = 2, c = -48; or you could multiply by -1 first, giving: x^2 - 2x + 48 = 0 Then a = 1, b = -2, c = 48; it turns out that there are no real roots -- it has only complex roots, which are: x = (1 + i√47) and (1 - i√47)

5x + 2x + 6 = 48 7x + 6 = 48 ....Because you simplify 5x + 2x 7x = 42 ....Because you subtract 6 from both sides to help isolate x x = 6 ....Because you divide both sides by 7 to isolate the x.

The expression is -x² + 2x + 48. Factor out -1 to get: -(x² - 2x - 48) Find two integers such that the product is -48 and the sum is -2. They are -8 and 6. Then, we can rewrite the expression as: -(x² - 8x + 6x - 48) Factoring-by-grouping, we obtain: -(x(x - 8) + 6(x - 8)) = -(x + 6)(x - 8) [Collect x and 6 and group x - 8.]

52 = 2x + (6x +4) 52 = 2x + 6x + 4 (can skip this step) 52 = 8x + 4 52 - 4 = 8x 48 = 8x 48/8 = x (can skip this step) 6 = x

X is the most famous variable in algebra, and a variable is a letter that stands for a number. It is used for you to apply methods of problem solving to get the answer, and the answer will be what x stands for. For example, if you see the problem 48-2x=100, you know you have to solve for x. The next step would be to subtract 48 from both ends of the equation, so you get (48-2x) -48= (100) -48 ---> -2x=52. Then you divide each side by -2 to get x by itself ---> -2x/2=52/-2 ---> x= -26. So you can see that x is not one specific number, it is just a variable.

3x+12=x+48: 3x-x=-12+48 2x=36 x=18

(2x) + (2x+2) + (2x+4) + (2x+6) + (2x+8) = 26010x + 20 = 26010x = 240x = 24The integers are 48, 50, 52, 54, and 56

the answer is 6

....................48...................../\...................4 x 12 ................../\ ...../\...............2 x 2 2 x 6............................/\ .........................2x 3 Thus, the prime factorization of 48 is 2x2x2x2x3 or 24x3.

Let the number of ducks be x, so that Robert has 12 - x rabbits. Since rabbits have 4 legs and ducks have 2 legs, we have: 2x + 4(12 - x) = 42 2x + 48 - 4x = 42 -2x + 48 = 42 (subtract 48 to both sides) -2x = -6 (divide by -2 to both sides) x = 3 Thus, Robert has 3 ducks and 9 rabbits.

x=-24. x+56=8-x therefore x+56-8=x and x+x+56-8=0. to make things easier, 2x+48=0 and you get 2x=-48. divide -48 by 2 and x=-24.

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4